Preliminary data on terrestrial isopods from some railways in Dobruja, eastern Romania - Daniel-Răzvan POP; Alexandra-Roxana-Maria MAIER; Achim-Mircea CADAR; Sára FERENȚI (Studia Universitatis Babeș-Bolyai. Biologia)
In July 2020 we analyzed the terrestrial isopod assemblages from different (mostly abandoned) railway constructions in Dobruja, eastern Romania. We identified 10 terrestrial isopod species, of which the most abundant and frequent were Porcellionides pruinosus (Brandt, 1833) and Armadillidium vulgare Latreille, 1804. We identified species that, in Romania, are present only in Dobruja: Leptotrichus pilosus Dollfus, 1905 and Trachelipus squamuliger (Verhoeff, 1907). Most of the species are common, generalist or synanthropic, connected to dry and open habitats. In abandoned railway-stations the number of species/samples was low (at most two), but at the base of a stone railway bridge in Babadag forest six species were found.